Evaluation of collector spacing, positioning, and nozzle selection methods on water distribution uniformity in center pivots - Lucas Maltoni Andrade; Rubens Alves de Oliveira; Fernando França da Cunha; Luis César Dias Drumond; Paulo Roberto Cecon; Job Teixeira de Oliveira; Catariny Cabral Aleman (PLoS ONE, 2025)
Proper design and periodic evaluation of center pivot irrigation systems are essential for ensuring uniform water distribution and improving water use efficiency in irrigated agriculture. This study assessed the impact of collector spacing and sampling methods, including a single-level collector line and combinations of multiple lines at different irrigated locations, on water distribution uniformity. Additionally, strategies for selecting emitter nozzles were analyzed. Uniformity assessments were conducted on two center pivots (P180 and P360) using collectors spaced at 1 m, with simulated spacings of up to 12 m by omitting intermediate readings. Collector lines were placed perpendicular to the pivot’s movement at 50% regulation and were evaluated three times. Data were analyzed individually for each line position and in groups, following layout recommendations from the literature. The mean water depth (LM), weighted mean depth (LW), and modified Christiansen’s uniformity coefficient (CUCHH) were used as evaluation metrics. Flow rate measurements were performed, with three repetitions per nozzle number. Nozzle selection considered the required flow rate and nozzle diameter for both constant and doubled spacing between emitters in the first two spans. Measured flow rates resulted in higher simulated water depths and lower CUCHH values compared to simulated reference flow rates. However, the average field CUCHH exceeded 90% for both pivots, being classified as excellent. Evaluation methods combining different collector line positions showed no significant differences between means, nor did the combined effect of collector spacing and single-line positioning. No significant differences were found between collector spacings alone. However, collector line positioning influenced results, with P180 showing differences in LW and P360 in LM, LW, and CUCHH. Estimated evaporation and wind drift losses were 14.21% for P360 and 13.49% for P180. The evaluated nozzle selection combinations showed a theoretical CUCHH higher than the simulated values based on the original nozzle listing for both pivots.